Wheel Running and Environmental Complexity as a Therapeutic Intervention in an Animal Model of FASD - Gursky, Zachary H. (J Vis Exp, 2017)
Aerobic exercise (e.g., wheel running (WR) extensively used in animal research) positively impacts many measures of neuroplastic potential in the brain, such as rates of adult neurogenesis, angiogenesis, and expression of neurotrophic factors in rodents. This intervention has also been shown to mitigate behavioral and neuroanatomical aspects of the negative impacts of teratogens (i.e., developmental exposure to alcohol) and age-related neurodegeneration in rodents. Environmental complexity (EC) has been shown to produce numerous neuroplastic benefits in cortical and subcortical structures and can be coupled with wheel running to increase the proliferation and survival of new cells in the adult hippocampus. The combination of these two interventions provides a robust "superintervention" (WR-EC) that can be implemented in a range of rodent models of neurological disorders. We will discuss the implementation of WR/EC and its constituent interventions for use as a more powerful therapeutic intervention in rats using the animal model of prenatal exposure to alcohol in humans. We will also discuss which elements of the procedures are absolutely necessary for the interventions and which ones may be altered depending on the experimenter's question or facilities.